5a-5+2a-7=

Simple and best practice solution for 5a-5+2a-7= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5a-5+2a-7= equation:


Simplifying
5a + -5 + 2a + -7 = 0

Reorder the terms:
-5 + -7 + 5a + 2a = 0

Combine like terms: -5 + -7 = -12
-12 + 5a + 2a = 0

Combine like terms: 5a + 2a = 7a
-12 + 7a = 0

Solving
-12 + 7a = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 7a = 0 + 12

Combine like terms: -12 + 12 = 0
0 + 7a = 0 + 12
7a = 0 + 12

Combine like terms: 0 + 12 = 12
7a = 12

Divide each side by '7'.
a = 1.714285714

Simplifying
a = 1.714285714

See similar equations:

| 2x+x*3=2700 | | x^06=0.75 | | 10*x+6*(0.8-t)=6 | | 2x^2-5x+28=0 | | 6lny=3lne^2-9lnx | | x+y+6+5x+2y=180 | | 15d^-5/5d^-8 | | 5x+2y=3x-6 | | 5x+2(x-20)=380 | | 3x^3+3x^2+4x=16 | | 2x+(x+60)+(3x-30)=180 | | 0.6g+11=-5 | | X/a-1= | | 7.8/7.41 | | 5a+(2a-5)-(a-3)=16 | | 7(4y-9)-(4y+8)= | | b^2-7b-36=0 | | (e-b)(c-d)= | | 21-6x=9 | | -243^(3/5) | | 3y-1+2x-4+x+3+15= | | 8x+46=5(x+5) | | 3n-4l= | | 6x^2=15 | | 6.1x-1.5=10.7 | | 2x+4=12+x | | (3^√7y^5)/(3^√64x^6) | | 6(4z-1)-5(z+3)=12(z+1) | | 4+7(x-1)=4-9(x-5) | | 9z-5=16+6z | | (y^2+4)=2y^2-y-10 | | 4*(2x-3)=5(x+2) |

Equations solver categories